Replication studies in economics—How many and which papers are chosen for replication, and why? - Frank Mueller-Langer; Benedikt Fecher; Dietmar Harhoff; Gert G. Wagner (Research Policy, 2019)
We investigate how often replication studies are published in empirical economics and what types of journal articles are replicated. We find that between 1974 and 2014 0.1% of publications in the top 50 economics journals were replication studies. We consider the results of published formal replication studies (whether they are negating or reinforcing) and their extent: Narrow replication studies are typically devoted to mere replication of prior work, while scientific replication studies provide a broader analysis. We find evidence that higher-impact articles and articles by authors from leading institutions are more likely to be replicated, whereas the replication probability is lower for articles that appeared in top 5 economics journals. Our analysis also suggests that mandatory data disclosure policies may have a positive effect on the incidence of replication.
Keywords: A1; B4; C12; C13; 330; Replication; Economics of science; Science policy; Economic methodology